DESIGN OF ELASTIC RING CLAMPING STRUCTURE FOR PIEZOELECTRIC BENDING EFFECT - GAO ChangYin; WU XiaoLing (Jixie qiangdu)
In order to verify the bending effect of quartz wafer,a special elastic ring clamping structure was designed to install and position the sensitive element. According to elastic mechanics and piezoelectricity,the calculation formula of bending stress and polarization of quartz wafer were deduced and the stress analysis of the elastic ring wafer clamping structure was carried out. In order to reduce the influence of structural deformation on sensor application performance,using the energy principle of elastic mechanics the static stiffness formula of the elastic ring wafer clamping structure under load was calculated. Using the finite element method the strength and stiffness of the elastic ring wafer clamping structure was verified. The theoretical calculation,finite element analysis and experimental measurement results show that the rigidity of the elastic ring wafer clamping structure is more than 10 kgf/um,which meets the requirements of sensor design. The research can provide technical support for the structural design of the new cantilever force sensor and micro actuator.